Non-growers' perspectives on home gardening: Exploring for future attraction - V.D. Nirusha Ayoni; Nurul Nadia Ramli; Mad Nasir Shamsudin; Ahmad Hanis Izani Abdul Hadi (Journal of Regional and City Planning, 2023)
To achieve urban sustainability, growing vegetables at home is a practical necessity. Understanding why people are hesitant to participate in urban vegetable growing is vital to reviving this practice. An in-person survey was conducted among 244 people who do not garden at home in Sri Lanka’s Colombo district to determine their perception of not gardening. Analysis was performed with exploratory factor analysis followed by binary logistic regression. According to the study, unrealized benefits and knowledge and experience challenges cause demotivation. The respondents had favorable attitudes toward urban agriculture; their interests appear to be aligned with urban agriculture and motivation should be able to entice them. The most viable way to attract them and ensure that they reap the economic and social benefits of urban home gardening appears to be to provide knowledge and hands-on experience. Younger people, private sector workers, and single homeowners are specific population segments that can be targeted for this motivation effort. The analysis further revealed that agriculture demonstrations in an urban setting inspire non-growers to practice urban agriculture.